The “right way” of Hermetism: disputes on Gnostic’s, Pagan’s and Christian’s (re-)visions of the Hermetic phonomenon in late antiquity - Pereira, Ronaldo Guilherme Gurgel (2013)
This paper aims to understand the phenomenon of Hermetism though the perspective of its process of reception and reproduction in society. It will explore the phenomenon that was the transformation of the Hermetica into a social discourse. The so-called technical and philosophical Hermetica are texts. A text is the result of a production: it is composed by men, and addressed to men. It is important to consider the intentions and values present in a text’s production, and to understand that its process of reception and reproduction in society are, in fact, complex and dynamic. A text must be viewed as not being simply a reflection of the society into which it is inserted, but rather as an active form of social mobilization. After a text’s production, it is presented to a society where different groups can participate in its process of reception and reproduction, or “textual circularity”. Then, different interpretations concerning the texts’ intentions can be proposed to society throughout the process of debatemic.